2021
DOI: 10.1002/esp.5204
|View full text |Cite
|
Sign up to set email alerts
|

Controls on the development of continuous gullies: A 60 year monitoring study in the Moldavian Plateau of Romania

Abstract: Gully erosion is a major environmental threat on the Moldavian Plateau (MP) of eastern Romania. The permanent gully systems consist of two main gully types. These are: (1) discontinuous gullies, which are mostly located on hillslopes and (2) large continuous gullies in valley bottoms. Very few studies have investigated the evolution of continuous gullies over the medium to longer term. The main objective of this study was to quantitatively analyse the development of continuous gullies over six decades . The ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
(51 reference statements)
0
5
1
Order By: Relevance
“…This result was close to the result reported by Hu et al [39] and Wu et al [40] in rolling hill areas in black soil of northeast China [39,40], and it was also within the range of Vanmaercke et al [6] who reported that linear, areal, and volumetric migration rate were 0.01-135 m yr −1 , 0.01-3628 m 2 yr −1 and 0.002-47430 m 3 yr −1 , respectively, through compiling the 933 individual gullies from 70 study areas in 25 countries of six continents that reflected a wide range of environmental conditions and gully headcut retreat globally. However, our results were distinctly greater than the result in the other study areas worldwide [12,[54][55][56][57]. For example, Frankl et al [56] found that the linear, areal, and volumetric retreat rate were 0.34 m yr −1 , 1.70 m 2 yr −1 and 5.20 m 3 yr −1 over the rainy reason of 2010, respectively, while larger rates were found during medium to long time periods (1-47 years), with averages of 3.8 m yr −1 , 31.5 m 2 yr −1 and 47.7 m 3 yr −1 in northern Ethiopia, respectively.…”
Section: Gully Headcut Migration and Its Response To Influencing Factorscontrasting
confidence: 93%
“…This result was close to the result reported by Hu et al [39] and Wu et al [40] in rolling hill areas in black soil of northeast China [39,40], and it was also within the range of Vanmaercke et al [6] who reported that linear, areal, and volumetric migration rate were 0.01-135 m yr −1 , 0.01-3628 m 2 yr −1 and 0.002-47430 m 3 yr −1 , respectively, through compiling the 933 individual gullies from 70 study areas in 25 countries of six continents that reflected a wide range of environmental conditions and gully headcut retreat globally. However, our results were distinctly greater than the result in the other study areas worldwide [12,[54][55][56][57]. For example, Frankl et al [56] found that the linear, areal, and volumetric retreat rate were 0.34 m yr −1 , 1.70 m 2 yr −1 and 5.20 m 3 yr −1 over the rainy reason of 2010, respectively, while larger rates were found during medium to long time periods (1-47 years), with averages of 3.8 m yr −1 , 31.5 m 2 yr −1 and 47.7 m 3 yr −1 in northern Ethiopia, respectively.…”
Section: Gully Headcut Migration and Its Response To Influencing Factorscontrasting
confidence: 93%
“…The most recent and impactful floods in Northern Serbia took place along the Danube and Tisa floodplains in 2013 [ 105 ], and their tributaries in 2014 [ 106 ]. Soil erosion and landslides are widespread in both regions due to a large spectrum of natural settings such as geological structure and lithology [ [107] , [108] , [109] ], relief fragmentation, soil properties, climate and hydrographic network particularities, but also due to the influence of anthropogenic factors [ [110] , [111] , [112] ].…”
Section: Regional Settingsmentioning
confidence: 99%
“…By using the data collected from the field, the gully erosion in the Puriceni-Bahnari catchment was drawn up. Thus, the presence of the two main gully types that are specific to the Barlad Plateau can be noticed, namely, continuous gullies on the valley bottom [50] and discontinuous gullies on the valley side [51] (Figure 8). At the catchment level, the mean value of annual soil loss on the agricultural land due to soil erosion amounted to 15.46 t•ha −1 •yr −1 (13,500 t•yr -1 ).…”
Section: Gully Erosionmentioning
confidence: 99%